Affective Experiences of International and Home Students During the Information Search Process. Issue 4 (2nd October 2017) - Haley, Adele Nicole; Clough, Paul
ABSTRACT: An increasing number of students are studying abroad requiring that they interact with information in languages other than their mother tongue. The UK in particular has seen a large growth in international students within Higher Education. These nonnative English speaking students present a distinct user group for university information services, such as university libraries. This article presents the findings from an in-depth study to understand differences between the search processes of home and international students. Data were collected using an online survey and diary-interview to capture thoughts and feelings in a more naturalistic way. International students are found to have similar information search processes to those of home students, but sometimes face additional difficulties in assessing search results such as confusion when dealing with differing cultural perspectives. The potential implications for information service providers, particularly university libraries, are discussed, such as providing assistance to students for identifying appropriate English sources.